Drug identifier the premier tool for drug identification 2012 (St. Louis, MO : Wolter Kluwer Health, 2012)
Provides fast identification of drugs by searching through more than 5,000 color images by shape, generic or brand name, manufacturer, color, imprint, NDC code, coatings and scoring
Single-user CD-ROM for Windows
Keywords: Catalogs, Drug; Pharmaceutical preparations